History of the Development of Education in Indonesia - Sopia Larasati; Muhammad Al Mighwar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research aims to describe and analyze how and what Indonesian education was like in ancient times, Japanese colonial, Dutch colonial, movement, development and reform. The results of this research are that the history of education in Indonesia does not only occur in one period, but as the development of the era of education in Indonesia has changed from time to time. This research method uses research specification methods, data collection methods and data analysis. Likewise, the conclusion of this journal is described as to (1) help understand the world of society (2) help understand identity (3) become informed citizens (4) and build good citizenship